SUCCESSFUL MACROVASCULAR PENILE REIMPLANTATION AFTER TRAUMATIC AMPUTATION IN A YOUNG MALE - Shamsher, Muhammad Asaad; Shinwari, Sajjad Muhammad Khan; Ijaz, Tariq (Khyber Journal of Medical Sciences, 2024)
Penile amputation is an uncommon occurrence that arises from acts of self-mutilation, unintentional trauma, or deliberate assault. In recent advances, multiple reconstructive techniques provide excellent outcomes for penile re-plantation. Here, we present a case of successful penile re-plantation and urethroplasty following 24 hours of ischemia in a 22-year-old male with complete urethral injury and a partially amputated penis. As far we know , this is one among the longest documented ischemia time for successful macrosurgical penile re-plantation. After 6 weeks of penile re-plantation, the patient recovered well and showed normal urination, erectile function, return of sensations, and satisfactory cosmetic outcome. Penile amputation injuries should be managed in a specialist center with expert urological and plastic surgeons of micro/macrosurgical reconstruction. The main aim of this study is to evaluate the treatment regimen and prognosis of macrosurgical re-plantation of penile stump.